A binary readout chip for silicon microstrip detector in proton imaging application. (11th January 2017) - Sipala, V.; Bruzzi, M.; Bondì, M.; Bonanno, D.; Cadeddu, S.; Carpinelli, M.; Cirrone, G.A.P.; Civinini, C.; Cuttone, G.; Lai, A.; Leonora, E.; Presti, D. Lo; et al.
Abstract: The mixed-signal PRIMA-chip has been developed for sensitive-position silicon detector in proton imaging application. The chip is based upon the binary readout architecture which, providing fully parallel signal processing, is a good solution for high intensity radiation application. It includes 32-front-end channels with a charge preamplifier, a shaper and a comparator. In order to adjust the comparator thresholds, each channel contains a 8-bit DAC, programmed using an I2C like interface. The PRIMA-chip has been fabricated using the AMS 0.35 μ m standard CMOS process and its performances have been tested coupling it to the detectors used in the tracker assembled for the pCT (proton Computed Tomography) apparatus.